2015
DOI: 10.1038/srep17628
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of weighted networks by a modified sandbox algorithm

Abstract: Complex networks have attracted growing attention in many fields. As a generalization of fractal analysis, multifractal analysis (MFA) is a useful way to systematically describe the spatial heterogeneity of both theoretical and experimental fractal patterns. Some algorithms for MFA of unweighted complex networks have been proposed in the past a few years, including the sandbox (SB) algorithm recently employed by our group. In this paper, a modified SB algorithm (we call it SBw algorithm) is proposed for MFA of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…In order to determine the multifractal dimensions of our complex network, we chose this adapted sandbox algorithm because it is precise, efficient and practical. Moreover, a study by Song et al [2] has shown that this algorithm gives better results when it is used in unweighted networks, and this is our case.…”
Section: Sandbox Algorithm For Multifractal Analysis Of Complex Networksupporting
confidence: 56%
“…In order to determine the multifractal dimensions of our complex network, we chose this adapted sandbox algorithm because it is precise, efficient and practical. Moreover, a study by Song et al [2] has shown that this algorithm gives better results when it is used in unweighted networks, and this is our case.…”
Section: Sandbox Algorithm For Multifractal Analysis Of Complex Networksupporting
confidence: 56%
“…In the past few years, studies have surfaced where the concept of multifractality has been applied to complex networks [2,8,10]. In all cases, some of the networks studied required a dimension spectrum to characterise the self-similar properties.…”
Section: The Multifractal Spectrummentioning
confidence: 99%
“…We use the range of values suggested in the literature [10], starting at -10 and ending at +10, in step sizes of one.…”
Section: Algorithm 1 Sandbox Algorithm For Multifractal Analysis Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], the box covering algorithm was designed to measure the fractal of real networks, which is named as box dimension. Box covering and box dimension of complex networks have been widely studied [9][10][11][12]. On the one hand, box dimension and box covering algorithms have been extended or modified.…”
Section: Introductionmentioning
confidence: 99%